SPECIES OF AMPHIBIA IN COAL MINE RECLAMATION OF PT. BUKIT ASAM, TBK. TANJUNG ENIM, SOUTH SUMATERA - Hayati, Nur; Windusari, Yuanita; Dahlan, Zulkifli (BIOVALENTIA: Biological Research Journal, 2021)
Coal mining activities in South Sumatra are among others carried out by PT. Bukit Asam tbk, a coal company located in Tanjung Enim. The open pit/cast mining process has a negative impact on the environment, some of the impacts are land degradation, loss of vegetation, changes in microclimate and loss of biodiversity which includes diversity of flora and fauna, one of which is amphibians. One of the efforts to maintain and preserve environmental capabilities is to reclaim former mines. In accordance with Law No. 4 of 2009 concerning Mineral and Coal Mining requires mining companies to carry out reclamation and post-mining activities over the areas they cultivate. Reclamation-revegetation activities are efforts to improve microclimate conditions, improve soil fertility conditions. The recovery of environmental conditions is expected to bring back the wildlife that has been lost. The amphibian community is believed to be a bioindicator of the recovery of environmental conditions undergoing habitat changes. The research was carried out at the Bukit Asam coal mine reclamation area, Air laya site from February to March. The aim of the study was to see the types of amphibians found in the mine reclamation area. Sampling was carried out using the VES (Visual Enconter Survey) method. From the results obtained, there were 3 species from 2 members of the Order (Anura) and 2 members of the Family (Rinidae).